(untitled) (Biodiversitas Journal of Biological Diversity, 2015)
Muchlisin ZA, Batubara AS, Siti-Azizah MN, Adlim M, Hendri A, Fadli N, Muhammadar AA, Sugianto S. 20015. Feeding habit and length weight relationship of keureling fish, Tor tambra Valenciennes, 1842 (Cyprinidae) from the western region of Aceh Province, Indonesia. Biodiversitas 16: 89-94. The objective of the present study was to describe the aspects of feeding habit and lengthweight relationship of keureling fish Tor tambra, this information is crucial to plan a conservation startegy for this species. A series of samples were taken between June and September 2012 and February 2014 in the two main rivers of western Aceh i.e. the Sikundo and Nagan Rivers. A total of 48 and 38 fish were caught during the study in Nagan and Sikundo Rivers, respectively. Stomach content analysis suggested that freshwater green algae and earthworms were the main food items for T. tambra, indicating an omnivorous feeding habit. In addition, the length-weight relationship revealed that T. tambra has an allometric negative growth pattern from all populations, and the condition factors indicate the rivers are still in good condition and support fish life.